2006
DOI: 10.1186/1471-244x-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Morphological correlates to cognitive dysfunction in schizophrenia as studied with Bayesian regression

Abstract: Background: Relationships between cognitive deficits and brain morphological changes observed in schizophrenia are alternately explained by less gray matter in the brain cerebral cortex, by alterations in neural circuitry involving the basal ganglia, and by alteration in cerebellar structures and related neural circuitry. This work explored a model encompassing all of these possibilities to identify the strongest morphological relationships to cognitive skill in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…Control subjects were recruited among students, hospital staff members or from a population register. All controls with the exception of those recruited from a population register had earlier attended in biological research at the Karolinska Institute [22,[30][31][32]. The controls consisted of non-psychotic individuals unrelated to the patients.…”
Section: Participantsmentioning
confidence: 99%
“…Control subjects were recruited among students, hospital staff members or from a population register. All controls with the exception of those recruited from a population register had earlier attended in biological research at the Karolinska Institute [22,[30][31][32]. The controls consisted of non-psychotic individuals unrelated to the patients.…”
Section: Participantsmentioning
confidence: 99%
“…studies and in vivo brain imaging studies (Wolf et al, 2008;Kubicki et al, 2007;Whitford et al, 2007;Laywer et al, 2006;Bogerts et al, 1990a,b;Witthaus et al, 2008). However, the extent to which these findings are related to vulnerability for schizophrenia, as opposed to the disease progression, is less certain.…”
Section: Structural Brain Abnormalities In Schizophrenia Have Been Dementioning
confidence: 99%
“…A worse CPT performance has been associated with smaller prefrontal volume in patients with schizophrenia, 134 but not in studies that included patients with any psychosis 8,135,136 or healthy individuals. 8,[134][135][136] Studies in patients with schizophrenia, their unaffected co-twins and healthy controls have found no association between CPT performance and hippocampal volume.…”
Section: Continuous Performance Testmentioning
confidence: 99%
“…8,[134][135][136] Studies in patients with schizophrenia, their unaffected co-twins and healthy controls have found no association between CPT performance and hippocampal volume. 8,[134][135][136][137] These findings suggest that worse performance on the n-back task is associated with smaller prefrontal and medial temporal volumes and that worse CPT performance is associated with smaller prefrontal volume in patients with schizophrenia. Consistent with this evidence, a meta-analysis of fMRI studies reported that the dorsolateral prefrontal cortex and the anterior cingulate cortex were less activated during the n-back task in patients with schizophrenia.…”
Section: Continuous Performance Testmentioning
confidence: 99%